2020
DOI: 10.1016/j.amsu.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Presacral myelolipoma, case report and literature review

Abstract: Introduction Myelolipomas are very rare benign tumours consisting of hematopoietic cells and mature adipose tissues. They are most commonly found in the adrenal glands. However, there have been several reported cases of extra-adrenal myelolipomas, most commonly in the presacral region. Nearly all presacral lesions are small and asymptomatic; thus, most are discovered incidentally on imaging studies. Presentation of case We report two cases of presacral myelolipomas. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Myelolipoma is a rare benign tumor composed of nature adipose cells and a mixed proportion of myeloid and erythroid elements, usually occurring in the adrenal gland without endocrine function [2] , [3] . As reported in many studies [2] , [3] , [8] , EAMs have a woman predominance with the female to male ratio of 2:1, and are susceptible to the ages from 50 to 70 years. However, Cheng shen et al reported that EAMs mainly occurred in males between 50 and 70 years of age with the male to female ratio ranging from 2:1 to 1:1 [5] .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Myelolipoma is a rare benign tumor composed of nature adipose cells and a mixed proportion of myeloid and erythroid elements, usually occurring in the adrenal gland without endocrine function [2] , [3] . As reported in many studies [2] , [3] , [8] , EAMs have a woman predominance with the female to male ratio of 2:1, and are susceptible to the ages from 50 to 70 years. However, Cheng shen et al reported that EAMs mainly occurred in males between 50 and 70 years of age with the male to female ratio ranging from 2:1 to 1:1 [5] .…”
Section: Discussionmentioning
confidence: 77%
“…Extra-adrenal myelolipoma (EAM) is even rarer, accounting for about 15% of all myelolipomas, and the predilection sites include the presacral (40%), peritoneal (20%), and thoracic (15%) cavities [2] , [7] . They are more commonly reported in women aged between the fifth and seventh decade with a female/male ratio of 2:1 [3] , [8] . However, fewer than 10 cases of EAMs in the spinal or intraosseous regions had been described in sporadic case reports by 2021 [2] , [3] , [9] , [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Myelolipoma is a benign tumor composed of mature adipose tissue and hematopoietic cells, and the adrenal gland is the most common site of attack. In a few cases, it can also occur in extra-adrenal tissues, such as the presacral region, mediastinum, pelvic cavity, lung, liver, and spleen, of which the sacral anterior region is the most common [ 11 , 12 ]. To our knowledge, there have been fewer than 60 reported cases of extra-adrenal myelolipoma, predominantly affecting females and typically discovered between the ages of 50 and 70 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] 2021 Female 44 14 × 11 × 8 cm Abdominal pain CT + MRI Resection 2 Andriandi et al. [ 36 ] 2020 Female 48 1.8 × 3.3 × 1.8 cm Atypical lower back pain MRI Conservative, follow-up 3 Andriandi et al. 2020 Female 59 4.2 × 4.2 × 4.7 cm No symptoms CT + MRI Conservative, follow-up 4 Rizzo et al.…”
Section: Methodsmentioning
confidence: 99%